Plan Layout Generator (PLG) A Rule-Based Plan Layout Generator for Mardin Houses - Torus, Belinda; Colakoglu, Birgul (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
The work presented in this paper illustrates automation of specific architecture language rules. Medieval city of Mardin architecture is used as case for developing the program named Plan Layout Generator - PLG which generates new abstract layout alternatives of Mardin house aimed to be utilized in the preliminary design phase.
Keywords: Generative design; Mardin house typologies; rule-based design; Architecture